The Niger River basin : a vision for sustainable management - Andersen, Inger, 1958-; Golitzen, Katherin George (Directions in development (Washington, D.C.), 2005)
This book comprises two distinct elements. The first, and major, part of the book (chapters 1-3) is a unique and essential compilation of technical information and data on the entire Niger River system. It presents a comprehensive overview of the physical environment and hydrological functions of the watershed, thus providing the necessary background for examination of the challenges of resource management and development potential. The second part of the book (chapter 4) presents the fundamental challenges that the nine countries1 of the Basin face and are now addressing.